The boy problem : (notes and predictions of Tabitha Reddy) - Kinard, Kami (Scholastic Press, 2014)
Twelve-year-old Tabitha believes in signs and predictions, and, inspired by her best friend Kara, she is looking for the signs that will point her to the right boyfriend--and predict a successful conclusion to her quest.